Identifying and prioritizing the selection criteria of appropriate repair and maintenance methods for commercial buildings - Tamošaitienė, Jolanta; Sarvari, Hadi; Cristofaro, Matteo; Chan, Daniel W. M. (International Journal of Strategic Property Management, 2021)
All buildings require Repair and Maintenance (R&M) in their life cycle period. However, if R&M activities are not carried out properly, deterioration will occur, service life of buildings will be reduced, and maintenance costs will increase. Hence, selecting the appropriate R&M methods is pivotal, especially for developing countries, such as Iran, which are featured by highly constrained resources. The present study aims to identify and prioritize the main criteria for selecting the suitable R&M methods for Commercial Buildings (CBs), which is considered as a profound challenge for the Architecture, Engineering and Construction/Facility Management (AEC/FM) industry. A total of 20 senior experts in the AEC/FM industry and CBs in Iran were invited to participate in a Delphi survey to solicit their perceptions and opinions on the selection criteria. The total number of individual criteria identified is 16, which are further divided into five categories: human resources, flexibility and technical capability, risks, cost of maintenance, together with facilities and technology. Then, the Fuzzy Analytic Hierarchy Process (FAHP) technique was applied to prioritize the identified criteria. Among the 5 main selection criteria, the cost of maintenance is the most important criterion for selecting appropriate R&M methods for CBs whereas the criterion of human resources (HR) was recognized as the least important.